2020
DOI: 10.1177/2045894020973906
|View full text |Cite
|
Sign up to set email alerts
|

Rescue therapy with thrombolysis in patients with severe COVID‐19‐associated acute respiratory distress syndrome

Abstract: Acute respiratory distress syndrome (ARDS) in patients with Coronavirus disease 19 (COVID-19) is associated with an unusually high incidence of pulmonary embolism (PE) and microthrombotic disease, with evidence for reduced fibrinolysis. We describe seven patients requiring invasive ventilation for COVID-19 ARDS with pulmonary thromboembolic disease, pulmonary hypertension ± severe right ventricular (RV) dysfunction on echocardiography, who were treated with alteplase as fibrinolytic therapy. All patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Hypercapnia has also been linked with the development of ACP and is thought to represent one of the factors responsible for vasoconstriction and the augmentation of pulmonary arterial pressure ( Jardin and Vieillard-Baron, 2009 , Biswas, 2016 , Boissier et al, 2013 ). Furthermore, in our patient, rtPA treatment resulted in the reduction of ventilatory ratio and an improvement in oxygenation status; this concurs with another article that was published recently ( Price et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Hypercapnia has also been linked with the development of ACP and is thought to represent one of the factors responsible for vasoconstriction and the augmentation of pulmonary arterial pressure ( Jardin and Vieillard-Baron, 2009 , Biswas, 2016 , Boissier et al, 2013 ). Furthermore, in our patient, rtPA treatment resulted in the reduction of ventilatory ratio and an improvement in oxygenation status; this concurs with another article that was published recently ( Price et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…This observation positively correlates with SARS-CoV-2 infection, where a severe impairment in the coagulation system leading to thrombosis is frequently observed [43] . Indeed, heparin has been tested as a prophylactic treatment and was demonstrated to improve disease-specific mortality [44] . Heparin clearly emerged in our analysis, supporting the potential and accuracy of SAveRUNNER software in identifying repurposable drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that genetic deletion of the IL-6 receptor does not improve the prognosis of septic mice, while the application of soluble gp130-Fc can significantly reduce the survival rate of CLP mice, decreasing apoptosis of endothelial cells [ 22 ]. In addition, the cytokine storm contains a variety of other inflammatory factors (IL-8, IL-10, IFN-γ and MCP-1, TNF-α, IL-1, and IL-3) [ 23 ]. Blocking IL-6R with tocilizumab alone may be insufficient to improve the prognosis of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%